1998
DOI: 10.1006/gcen.1997.7032
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Cortisol Concentrations and Ontogeny of Aggressive Behavior in Yellowtail (Seriola quinqueradiataTemminck & Schlegel; Carangidae)

Abstract: Ontogenetic changes in whole-body immunoreactive cortisol concentrations (IRC) and aggressive behavior were examined in yellowtail Seriola quinqueradiata (Temminck & Schlegel; Carangidae). Baseline IRC significantly increased during the transition from larval to juvenile stage, and was correlated with the onset of aggressive behavior. Handled fish (13.1±2.6 ng/g tissue) showed a IRC level about three times higher than unhandled fish (4.7±1.4 ng/g tissue), indicating that whole body immunoreactive cortisol lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
19
2
Order By: Relevance
“…Most studies investigating the effect of conspecific density include the cannibalism phase (e.g. Hecht et al 1996, Sakakura et al 1998, Baras et al 2003, Fessehaye et al 2006, Szkudlarek & Zakęś 2007, Kotani et al 2009); and therefore are not directly comparable with the present study.The larval and juvenile mortality rates observed in the present study (approximately 5 to 12% d -1 ) were in the lower range of that reported to occur in the wild for marine pelagic fish (Houde 2002). At the end of the trial there was considerable variation in median weight and mortality within and between treatments, and the mortality rate was so variable that the relative density differences between treatments diminished completely.…”
contrasting
confidence: 56%
“…Most studies investigating the effect of conspecific density include the cannibalism phase (e.g. Hecht et al 1996, Sakakura et al 1998, Baras et al 2003, Fessehaye et al 2006, Szkudlarek & Zakęś 2007, Kotani et al 2009); and therefore are not directly comparable with the present study.The larval and juvenile mortality rates observed in the present study (approximately 5 to 12% d -1 ) were in the lower range of that reported to occur in the wild for marine pelagic fish (Houde 2002). At the end of the trial there was considerable variation in median weight and mortality within and between treatments, and the mortality rate was so variable that the relative density differences between treatments diminished completely.…”
contrasting
confidence: 56%
“…These results show that social stress may induce lipid peroxidation. Social stress is well recognized as a potential stressor for some fish species (Hoglund et al, 2001;Volpato & Fernandes, 1994;Damsgard & Arne Mikol, 1998;Sakakura et al, 1998;Overli, et al, 1999), but the magnitude of stress is related to social status (Fernandes & Volpato, 1993;Sakakura et al, 1998;Sakakura & Tsukamoto, 1999). The stress response is a catabolic reaction (Vijayan et al, 1997), and if subordinates show a response of higher magnitude, they may have an increase in metabolism inducing higher lipid peroxidation than in dominant fish.…”
Section: Discussionmentioning
confidence: 99%
“…Social stressors also affect fish metabolism, causing a physiological stress state (Fernandes & Volpato, 1993;Alvarenga & Volpato, 1995;Giaquinto & Volpato, 1997;Damsgard & Arne Mikol, 1998;Overli et al, 1998;Sakakura et al, 1998;Overli et al, 1999;Sakakura & Tsukamoto, 1999;Hoglund et al, 2000). The physiological "fight or flight" responses to a stressor include catabolic reactions (Vijayan et al, 1997), and the magnitude of stress responses to social stress is inversely related to social status (Fernandes & Volpato, 1993;Sakakura et al, 1998;Sakakura & Tsukamoto, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that one-year-old masu salmon that lost an aggressive interaction initiated downstream migratory behavior in an artificial raceway (Munakata et al, 2000). In addition, cortisol levels in individuals that recently lost a fighting contest were elevated in rainbow trout (O. mykiss; Øverli et al, 2004) and other species (Sakakura et al, 1998;Schuett and Grober, 2000), and testosterone levels in winners of aggressive interactions were generally lower than in losers (Hsu et al, 2006). Thyroid hormones have also been known to decrease the aggressive behavior of four salmonids during smoltification (Hutchison and Iwata, 1998).…”
Section: Introductionmentioning
confidence: 99%